The powerful of social media usage towards islamophobia understanding among Malaysian netizens / Mohd Shaiful Zainudin ...[et al.] - Zainudin, Mohd Shaiful; Mohd Azizi, Muhammad Zul Azri; Zakaria, Norhazieram; Abd. Latiff, Zulkifli (Centre For Media And Information Warfare Studies, 2021)
Understanding the focus of social media for Islamophobia issues in Malaysia and how they are conducted is important to understand where the research is headed. Hence, this study is aimed to understand the role of social media, identify Islamophobia issues and identify the causes and effects of Islamophobia in Malaysia. Meta-analysis is employed as a methodology and 152 articles published between 2007 and 2020 are investigated through content analysis. Several types of the articles acknowledged that social media has contributed to efforts to promote Islamophobia and have the potential to promote peace. The results are interpreted with descriptive statistics. As a result, it is found that; (1) most of the studies incorporate Facebook, Twitter, and YouTube for social networking, (2) six types of Islamophobia issues occurred in Malaysia, (3) the effect of these issues was social media change society, socio-economy and mental and physical. Malaysian media should be commended for their past dedication and efforts in always being attentive to sensitive topics such as religion and language, cultural prejudice, and racism but need to have control mechanism.